Structural Oppression in Bernardine Evaristo’s Novel Girl, Woman, Other (2019) - Asih, Bunga Dewara; Al-Hafizh, Muhd. (English Language and Literature, 2021)
This research is an analysis of the novel Girl, Woman, Other (2019) by Bernardine Evaristo. The purpose of the analysis is to reveals the issue of structural oppression towards black women and the struggle against the structural oppression in the novel  Girl, Woman, Other (2019) by Bernardine Evaristo. The issue of structural oppression refers to the form of structural oppression against black women and the form of struggle that characters do against the oppression towards them. This analysis is using the concept of intersectionality from feminism study which proposed by Kimberlee Crenshaw. The analysis uses of the concept is based on the interpretation of text and context of the novel. The analysis also uses fictional devices such as plot and setting to expose the meaning. The result of this study shows the form of structural oppression against black women and the struggle that black women show against the oppression.